Review of the textbook written by Professor Ramūnas Palšaitis “Fundamentals of Business Logistics” - Bazaras, Darius (Transport, 2003)
The textbook “Fundamentals of Business Logistics”, written by professor Ramūnas Palšaitis appears as a very expected and useful publication. The lecturers and students were waiting for this publication for a long time, because till now we did not have such a systematized and particular monograph, which would analyse logistics and could be used for the logistics study process. By now, every known textbook and monograph of other authors was more or less acceptable for studying logistics, but in many cases it has some problematical points, it analyses only one point of the common logistics science, it is not of practical use and cannot be applied for every day activities. In the textbook “Fundamentals of Business Logistics” written by professor Ramunas Palšaitis we can find an orbicular view of the theoretical understanding of logistics and put it into practical use. Consequently, this publication could be useful for both students (during their study process) and businessmen in the business companies, who are active in the sphere of logistics.First Published Online: 19 Dec 2011